Antifungal and cytotoxic constituents from the endophytic fungus Penicillium sp. - Ehab S. Elkhayat; Asmaa Mohamed Goda (Faculty of Pharmacy, Cairo University, 2017)
New mellein derivative; 4-methylmellein (1) along with five known compounds: 4-hydroxymellein (2) and 6-hydroxymellein (3), tyrosol (4), cervesterol (5), and stigmast-4-ene-3-one (6) were isolated from the ethyl acetate extract of the endophytic fungus Penicillium sp. isolated from the leaf of Senecio flavus (Asteraceae). Structures were established by 1D and 2D NMR, in addition to UV, IR and MS spectrometry. Compounds (3, 4 and 6) were isolated for the first time from the genus Penicillium. Compounds 1-4 showed antifungal activity against F. oxysporum and variable activities against A. flavus and the yeast C. albicans. Compounds 1-3 showed cytotoxic activity against MCF-7 cell line.